Paedomorphic Facial Expressions Give Dogs a Selective Advantage - Waller, Bridget M.; Peirce, Kate; Caeiro, Cátia C.; Scheider, Linda; Burrows, Anne M.; McCune, Sandra; Kaminski, Juliane (PLOS ONE, 2013)
How wolves were first domesticated is unknown. One hypothesis suggests that wolves underwent a process of self-domestication by tolerating human presence and taking advantage of scavenging possibilities. The puppy-like physical and behavioural traits seen in dogs are thought to have evolved later, as a byproduct of selection against aggression. Using speed of selection from rehoming shelters as a proxy for artificial selection, we tested whether paedomorphic features give dogs a selective advantage in their current environment. Dogs who exhibited facial expressions that enhance their neonatal appearance were preferentially selected by humans. Thus, early domestication of wolves may have occurred not only as wolf populations became tamer, but also as they exploited human preferences for paedomorphic characteristics. These findings, therefore, add to our understanding of early dog domestication as a complex co-evolutionary process.